The senses as a resource of meaning in the construction of the Stranger: an approach from Georg Simmel’s relational sociology - Sabido Ramos, Olga (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2017)
This article explores the analytical relation between senses, space, and the stranger in Simmel’s relational thought. We can say that Simmel provides an analytical framework for thinking of how we create forms of socialization that take place from the senses. The senses mark areas of familiarity and strangeness among people and, the senses are a resource of meaning in the construction and exclusion of the stranger. Specifically, the article recovers Simmel's reflections regarding the relationship of estrangement that develops from the gaze, smell, and hearing, supplemented by recent empirical research in these fields and some examples related to Latin American cities.